Ground-State Proton Transfer of 7-Hydroxyquinoline Confined in Biologically Relevant Water Nanopools - Park, Sun-Young; Kwon, Oh-Hoon; Kim, Taeg Gyum; Jang, Du-Jeon (Journal of physical chemistry. C, 2009)
The ground-state reverse proton transfer of 7-hydroxyquinoline catalyzed by water confined in AOT reverse micelles has been investigated by measuring time-resolved transient-absorption spectra and kinetic profiles. The transfer time is profoundly retarded in water nanopools compared with that in bulk water (26 μs) although it diminishes with the size increase of the water nanopool. The spectral-shift time of tautomeric transient absorption agrees well with the proton transfer time. The probe molecule is subject to the local gradient of polarity, whose magnitude is altered with the sizes of water nanopools. Accordingly, the observations made in this study indicate the multidimensional character of reaction coordinates, in which solvent polarization coupled to charge transfer plays a seminal role in the control of overall proton-transfer dynamics. The retardation of proton transfer in water nanopools is ascribed to the increased formation energy of a charge-transferred optimal configuration, which is prerequisite to facile intrinsic proton transfer via tunneling.